Spatio-Temporal Detection of Vegetation Change and Recovery in Fire-Affected Peatlands of Sumatra, Indonesia - Setiawan, M.Sc, Dr. Yudi; Setiawan, Yudi; Kustiyo, Kustiyo; Hudjimartsu, Sahid Agustian; Handayani, Marshela Aida; Jamil, Awaludin; Putra, Erianto Indra (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Tropical peatlands are among the most fire-prone ecosystems in Southeast Asia, where recurrent burning causes long-term degradation, carbon loss, and biodiversity decline. Assessing spatio-temporal patterns of recovery is therefore essential for guiding effective peatland restoration and fire prevention strategies. This study investigated vegetation recovery dynamics in a fire-affected peatland in Sumatra, Indonesia. Multi-temporal satellite imagery was processed to extract the Enhanced Vegetation Index (EVI) and Normalized Burn Ratio (NBR). Fire frequency and severity were further analyzed through hotspot distributions and fire history. The results revealed that NBR and dNBR were highly effective in detecting burned areas and assessing severity, while EVI provided complementary perspectives on recovery trajectories. Vegetation in once-burned areas showed relatively steady regrowth, with EVI values approaching pre-fire levels after several years. In contrast, repeatedly burned areas exhibited slower and more heterogeneous recovery, with fluctuating EVI pattern reflecting vegetation growth succession. Field vegetation surveys confirmed that repeated fires drastically simplified forest structure, reducing tree and pole density and favoring shrubs and ferns such as Stenochlaena palustris and Melastoma malabathricum. Overall, the study demonstrates that fire frequency and severity are critical determinants of peatland recovery. The EVI offers valuable insights into vegetation dynamics, while NBR provides reliable fire history mapping. These findings underscore the importance of combining spectral indicators with ground-based vegetation data for long-term monitoring and highlight the need for targeted restoration strategies, including hydrological rewetting and assisted natural regeneration, in repeatedly burned peatlands.